PENGEMBANGAN MEDIA BERBASIS AR PADA MATERI BANGUN DATAR PADA KELAS IV SD NEGERI 20 TANJUNG LAGO - Putri wana Rahmayanti; Yusni Arni; Clara Artika Wulan; Impi Yeni (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research aims to develop learning media based on Augmented Reality (AR) based learning media on flat building materials for grade IV students at SD Negeri 20 Tanjung Lago, which uses the Research and Development (R&D) method and the ADDIE development model (Analysis, Design, Development, Implementation, Research collected data through observation, interviews, and product trials of students. The results show that AR-based learning media can significantly improve students' understanding of the concept of flat shapes, with better student learning outcomes after using the media. Therefore, AR-based learning media can be an effective alternative to improve the quality of mathematics learning, especially the concept of flat shapes. This study suggests the use of augmented reality (AR) technology as an inventive and interactive learning tool.